Functional status impairment at six-month follow-up is independently associated with child physical abuse mechanism. (December 2021) - Jensen, Aaron R.; Evans, Lauren L.; Meert, Kathleen L.; VanBuren, John M.; Richards, Rachel; Alvey, Jessica S.; Holubkov, Richard; Pollack, Murray M.; Burd, Randall S.; ,; Carcillo, Joseph A.; Carpenter, Todd C.; et al.
Abstract: Background: Children with abusive injuries have worse mortality, length-of-stay, complications, and healthcare costs compared to those sustaining an accidental injury. Long-term functional impairment is common in children with abusive head trauma but has not been examined in a cohort with heterogeneous body region injuries. Objective: To assess for an independent association between child physical abuse and functional impairment at discharge and six-month follow-up. Participants and setting: Seriously injured children (<15 years) treated at seven pediatric trauma centers. Methods: Functional status was compared between child physical abuse and accidental injury groups at discharge and six-month follow-up. Functional impairment was defined at discharge ("new domain morbidity") as a change from pre-injury ≥2 points in any of the six domains of the Functional Status Scale (FSS), and impairment at six-month follow-up as an abnormal total FSS score. Results: Children with abusive injuries accounted for 10.5% (n = 45) of the cohort. New domain morbidity was present in 17.8% (n = 8) of child physical abuse patients at discharge, with 10% (n = 3) of children having an abnormal FSS at six-months. There were no differences in new domain morbidity at hospital discharge between children injured by abuse and or accidental injury. However, children injured by physical abuse were 4.09 (2.15, 7.78) times more likely to have functional impairment at six months. Conclusions: Child physical abuse is an independent risk factor for functional impairment at six-month follow-up. Functional status measurement for this high-risk group of children should be routinely measured and incorporated into trauma center quality assessments.